An abstract-argumentation-based approach for the portfolio selection problem - Morveli-Espinoza, Mariela; Possebom, Ayslan T.; Tacla, Cesar A. (Anais do Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações (WESAAC), 2017)
A portfolio problem is about selecting one or several out of a set of possible items, considering some constraints, and where outcomes are determined by a form of aggregating the properties of the items selected. In this paper, we aim to study the use of abstract argumentation theory for a simplified version of the portfolio selection problem, where the conflicts among the arguments (items) can be seen as constraints and the value of each argument (item) can determine the set of acceptable (selected) ones. An example is provided to demonstrate the performance of our approach.